Stability of breathers in simple mechanical models for DNA - Slade, G. G. [UNESP]; Drigo Filho, Elso [UNESP]; Ruggiero, José Roberto [UNESP] (Iop Publishing Ltd, 2010)
This work studies through the Floquet theory the stability of breathers generated by the anti-continuous limit. We used the Peyrard-Bishop model for DNA and two kinds of nonlinear potential: the Morse potential and a potential with a hump. The comparison of their stability was done in function of the coupling parameter. We also investigate the dynamic behaviour of the system in stable and unstable regions. Qualitatively, the dynamic of mobile breathers resembles DNA.